Planning for Academic Supervision by Supervisors for Junior High School Christianity Teachers - Wolter Weol; Benny B. Binilang; F. J.A. Oentoe; Treesje K. Londa (International Journal of Education, Information Technology, and Others, 2020)
This study aims to obtain an in-depth picture of the implementation of supervisory academic supervision of PAK teachers in Junior High School (SMP) Negeri 1 Amurang. Associated with obtaining information and descriptions clearly and systematically in using a qualitative approach where as a researcher tries to photograph, describe and interpret every phenomenon of the object under study in accordance with the objective situation and conditions. The research design of a multisite study is a qualitative research design involving several sites and research subjects who are assumed to have the same characteristics. Multisite study is one type of qualitative research, especially for constructing and developing theories based on several similar research backgrounds so that it can produce theories that can be transferred to situations with a broader and general scope. In the context of this multisite study, the research on the academic supervision of Christian religious teachers in three junior high schools has similarities with one another. The results showed that planning for academic supervision by PAK supervisors for Christian religious teachers at State Junior High Schools in South Minahasa was generally carried out because it has become the main task, function and responsibility of the supervisor; based on the program from the ministry of religion which is embodied in the supervisory program and follows the academic calendar of educational units